Conceptual hydrogeology model to Bajo Cauca antioqueño: a tropical aquifer system - Teresita Betancur; Oscar Mejia; Carlos Palacio (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
This paper presents a hydrogeology conceptual model of Bajo Cauca Antioqueño obtained from hydrogeology exploration work and geostatistics modeling.